Analysis of a Double-sided Metasurface Structure for the Design of Multifunctional and Directional Insensitive Devices - Nilotpal; Chakrabarti P.; Bhattacharyya S. (My University, 2025)
A dual-sided metasurface structure, consisting of two different sets of sub-wavelength periodic metallic patterns on its two sides, can offer a promising platform for the design of multifunctional and directional insensitive devices. This paper presents an elaborative study of the structural and mathematical analyses of the frequency response of a dual-sided metasurface structure. It has been found that the ratio between resonating wavelength and the structure’s thickness plays a deterministic role in achieving multi-functionality in such designs. The paper further presents an equivalent circuit model of the dual-sided metasurface structure to mathematically analyze the role of impedance in achieving directional insensitivity in such devices. The proposed structural and mathematical analysis has been validated together by designing a directional insensitive rasorber in the latter half of the paper. The analyses done in this paper can open up a broad avenue for the research and development of metasurface-based directional insensitive multifunctional optoelectronics devices. © 2024 IETE.